Gliotoxin Induces Cofilin Phosphorylation to Promote Actin Cytoskeleton Dynamics and Internalization of Aspergillus fumigatus Into Type II Human Pneumocyte Cells - Zhang, Changjian; Chen, Fangyan; Liu, Xiaoyu; Han, Xuelin; Hu, Yingsong; Su, Xueting; Chen, Yong; Sun, Yansong; Han, Li (Frontiers in Microbiology, 2019)
Aspergillus fumigatus is able to internalize into lung epithelial cells to escape from immune attack for further dissemination. We previously reported that gliotoxin, a major mycotoxin of A. fumigatus, promotes this internalization; however, the mechanism remained unclear. Here, we report that gliotoxin is able to induce cofilin phosphorylation in A549 type II human pneumocytes. Either too high or too low a level of cofilin phosphorylation blocked the gliotoxin-induced actin cytoskeleton rearrangement and A. fumigatus internalization. LIM domain kinase 1 (LIMK1) and its upstream small GTPases (Cdc42 and RhoA, but not Rac1) predominantly mediated the gliotoxin-induced cofilin phosphorylation and A. fumigatus internalization. Simultaneously, gliotoxin significantly stimulated an increase in cAMP; however, adding an antagonist of PKA did not block gliotoxin-induced A. fumigatus internalization. In vivo, exogenous addition of gliotoxin promoted A. fumigatus invasion into the lung tissue and lung fungal burden in immunosuppressed mice. In conclusion, these data revealed a novel role of gliotoxin in inducing cofilin phosphorylation mostly through the Cdc42/RhoA-LIMK1 signaling pathway to promote actin cytoskeleton rearrangement and internalization of A. fumigatus into type II human pneumocytes.